APPLICATION OF PROBLEM-BASED LEARNING (PBL) MODEL TO IMPROVE THE ACTIVITY OF GRADE VIII STUDENTS IN THE LIGHT AND OPTICAL SYSTEM LEARNING MATERIAL - Shokhib Zaky Fananto; Samiaji Samiaji (Prodi Pendidikan IPA FMIPA Universitas Negeri Malang, 2022)
Learning based on actual problems experienced by students using problem-based learning models is believed to increase student participation in identifying problems and student activity in solving problems. This study aimed to increase the activeness of class VIII students in the material of light and optical instruments. The subjects of this study were 32 class VIII A students of SMPN 1 Karanggeneng, Lamongan. The study was conducted in the pre-, cycle I, and cycle II stages. Data collection techniques were carried out using activeness observation techniques, cycles I and II tests, and documentation. Data analysis techniques are used to compare the results of observations of student activity at the pre-cycle, cycle I, and cycle II stages. The results showed increased student activity in cycles I (74.55%) and II (85.27%). Several factors can influence student activity. Therefore, the role of teachers as facilitators is needed to determine learning strategies for student needs so that students can more readily accept and understand the material that will be delivered well. Applying the problem-based learning model can increase the activeness of class VIII students in the material on light and optical systems.